Schizophrenia and smoking: impact on negative symptoms - Miriam Saliba; Shafika Assaad; Chadia Haddad; Souheil Hallit; Dory Hachem; Georges Haddad (Centros de Integración Juvenil A.C., 2017)
Introduction: it has been hypothesized that individuals with schizophrenia use nicotine to reduce negative symptoms and improve cognitive function. There is an inconsistency in the literature suggesting that nicotine could help decrease negative symptoms in schizophrenic patients. Objective: to investigate the effects of nicotine on the expression of the negative symptoms in smokers and non-smokers with schizophrenia. Methods: a cross sectional study, conducted between April and August 2016, 100 inpatients with schizophrenia (54 smokers and 46 non-smokers) diagnosed according to DSM-V, at Psychiatric Hospital of the Cross Lebanon, were compared to changes in clinical parameters using CDSS, PANSS, and nicotine dependence using FTND. The Student's t-test was used to compare between 2 groups, while the ANOVA test was used to compare between 3 or more groups. For categorical variables, the chi-2 test was used. Results: the mean age was 47.16 years (SD = 7.14) for smokers compared to 47.02 years (SD = 7.92) for non-smokers. 64.8% of smokers were males versus 45.7% of non-smokers. Smoking (high nicotine dependence) significantly decreases the PANSS negative symptoms score between the 2 groups (p < .001), whereas it did not show a significant difference for the positive and the cognitive symptoms total score (p > .05 for both variables). Discussion and conclusion: this study is the first to investigate the relationship between the expression of negative symptoms in individuals with schizophrenia and smoking in Lebanon. Cigarette smoking rates remain remarkably high in patients with schizophrenia. Smoking is a complex process which involves psychopathological, biochemical and neuropharmacological aspects among schizophrenic patients. Further studies are needed to acknowledge these findings and the reasons behind it.----------------------- Antecedentes: se ha planteado la hipótesis de que los pacientes con esquizofrenia emplean la nicotina para reducir los síntomas negativos de su enfermedad y para mejorar su función cognitiva; sin embargo, no existe evidencia concluyente en la literatura sobre el vínculo entre el consumo de nicotina y la disminución de los síntomas negativos de la enfermedad. Objetivo: investigar los efectos de la nicotina en la expresión de síntomas negativos en pacientes con esquizofrenia, tanto fumadores como no fumadores. Método: se realizó un estudio transversal con 100 pacientes diagnosticados con esquizofrenia (54 fumadores y 46 no fumadores) en el Hospital Psiquiátrico de la Cruz, en Líbano, entre abril y agosto de 2016. Se utilizaron los instrumentos CDSS, PANSS y FTND para evaluar parámetros clínicos. Se emplearon las pruebas t de Student, ANOVA y chi-cuadrada para las comparaciones. Resultados: la edad media de los fumadores fue de 47.16 años (SD = 7.14) y la de los no fumadores de 47.02 años (SD = 7.9). 69.8% de los fumadores y 45.7% de los no fumadores fueron hombres. La alta dependencia de la nicotina se relacionó con la disminución de síntomas negativos evaluados con el PANSS entre los dos grupos (p < .001); no se encontraron diferencias significativas ni en los síntomas positivos ni con los cognitivos (p > .05 para ambas variables). Discusión y conclusiones: este estudio es el primero en investigar la relación entre la expresión de los síntomas negativos y el tabaquismo en pacientes con esquizofrenia en Líbano. El tabaquismo es un proceso complejo que involucra aspectos psicopatológicos, bioquímicos y neurofarmacológicos; las tasas de tabaquismo son considerablemente altas entre pacientes con esquizofrenia, por lo que son necesarios más estudios para reconocer estos hallazgos y sus bases.